(3aj GddgLGJ GdYQHjIs - (3CfjS, EHQGgjes ((3GdbGgQIs (3ecJHI GdCfLdh GdeUQjIs, 2010)
(3JfGhd GdcJGH (B"(3GddgLGJ GdYQHjI(B"(3, aHMK MGd GdYQHjI bHd GdESdGe, hhGbY GddgLGJ ajgG, hOQS eG HjfgG hHjf GdbQGAGJ GdbQBfjI ef UdGJ, hYQV Cge bVGjGgG aj HfjJgG hOdGdJgG heG HjfgG ef GJaGb hGNJdGa, Ke GfJgi Edi Cf GdYfGUQ GdeTJQcI aj GddgLGJ GdYQHjI GdMOjKI JfJej Edi dgLGJ YQHjI bOjes
12
Keywords: (3GdbQBf hGddZIs; (3GddZI GdYQHjIs -- (3GddgLGJs; (3GddgLI GdYQHjI GdHGFOIs